Structure of a membrane-bound menaquinol:organohalide oxidoreductase - Cimmino, Lorenzo (2023)
Funding Information: We thank the Dubochet Center for Imaging (DCI) in Lausanne for cryo-EM data collection. DCI is an initiative of the EPFL, University of Lausanne and University of Geneva. We also thank Kelvin Lau from PTPSP laboratory (EPFL) and the PCF laboratory (EPFL). This work was supported by the Swiss National Science Foundation (grant N° CRSII5_177195 and grant N° 310030_188548 to HS; grant N° 31003 A 173059 to CH), the Sino-Swiss Science and Technology Cooperation SSSTC (N° IZLCZ0_206089 to HS), the Fundação para a Ciência e Tecnologia for support through the MOSTMICRO-ITQB unit (UIDB/04612/2020 and UIDP/04612/2020 to AGD and IACP) and the Associated Laboratory LS4FUTURE (LA/P/0087/2020 to AGD and IACP). Funding Information: We thank the Dubochet Center for Imaging (DCI) in Lausanne for cryo-EM data collection. DCI is an initiative of the EPFL, University of Lausanne and University of Geneva. We also thank Kelvin Lau from PTPSP laboratory (EPFL) and the PCF laboratory (EPFL). This work was supported by the Swiss National Science Foundation (grant N° CRSII5_177195 and grant N° 310030_188548 to HS; grant N° 31003 A 173059 to CH), the Sino-Swiss Science and Technology Cooperation SSSTC (N° IZLCZ0_206089 to HS), the Fundação para a Ciência e Tecnologia for support through the MOSTMICRO-ITQB unit (UIDB/04612/2020 and UIDP/04612/2020 to AGD and IACP) and the Associated Laboratory LS4FUTURE (LA/P/0087/2020 to AGD and IACP). Publisher Copyright: © 2023, The Author(s).